KONSEP KENDIRI DAN KESEJAHTERAAN PSIKOLOGI REMAJA DELINKUEN DI SEKOLAH-SEKOLAH TUNAS BAKTI, SEMENANJUNG MALAYSIA - Kamarul Arifain, Siti Marhamah; Mokhtar, Muhammad Yasin Omar; Yusof, Faudziah; Abdullah, Norhasima (Jurnal 'Ulwan, 2024)
Self-concept and psychological well-being are closely intertwined because self-concept has a relationship with the psychological well-being of adolescents. This study uses the design of correlation studies through a cross-sectional design approach. In this study, 296 adolescents between the ages of 13 and 17 were selected using a stratified random sampling. The study locations involved were all Sekolah Tunas Bakti in Peninsular Malaysia. The results showed that the highest mean was 2.88, which is physical self-concept, followed by family self-concept with a mean of 2.43, while the third highest mean was personal self-concept at 2.38. Next, the social self-concept with a mean value of 2.37 followed by the moral self-concept with a mean value of 2.27 and lastly the lowest mean was the academic/employment mean of 2.17. While the results of the inference analysis using Pearson correlation analysis showed that there was a significant association of self-concept towards psychological well-being among delinquent adolescents in Peninsular Malaysia (r=0.57, k< .00). In conclusion, this study explains that self-concept that is positively related to psychological well-being in adolescents can have a positive impact in the future to the country thus helping the formation of a generation with good values and morals.